Pengolahan Limbah Cair Emulsi Minyak dengan Proses Membran Ultrafiltrasi Dua-tahap Aliran Cross-flow - Suprihanto Notodarmojo; Dini Mayasanthy; Teuku Zulkarnain (Journal of Mathematical and Fundamental Sciences, 2004)
A study on the use of cellulosa acetate membrane using cross-flow system to treat oil-water emulsion waste came from metal cutting process of automotive industry has been done. The objectives of this research are to treat oil water emulsion waste and to see the impact of pretreatment process to membrane performance. The separation mechanism of ultrafiltration process is filtration. The molecule which is smaller than membrane pore size will pass the membrane other wise, the bigger one will be rejected. The ultrafiltration process performance is determined by permeate fluks and rejection. The material of membrane used in this process is cellulosa acetate membrane with 12 % composition for first stage operation and 15 % one for second stage operation, each on 90 minutes operation time. Operation pressure used was 3,5 Bar. There are two type feeding operation treated by membrane, feeding without pretreatment and feeding with pretreatment. On the first stage membrane operation, waste without pretreatment applied flux at 17,03 L/m2.h, and for waste with pretreatment the applied flux was 59,05 L/m2.h. On the second stage membrane operation the applied flux of waste without pretreatment was 22,08 L/m2.h, and the flux of waste with pretreatment was 24,86 L/m2.h. Overall COD and surfaktan rejection involving two stage membrane operation, which COD rejection was 96,57% for waste without pretreatment, and surfactant rejection was 96,35 %. Meanwhile, for waste with pretreatment the COD rejection was 98,56 % and the surfactant rejection 97,44%. It is concluded that pretreatment process give a benefit to increase fluks and goof quality permeate.